ANALISIS PENGENAAN PAJAK PENGHASILAN (PPH) TERHUTANG SEBELUM DAN SESUDAH PENETAPAN PP NOMOR 46 TAHUN 2013 PADA APOTIK MUTIA - Adriansyah, Adriansyah (jurnal ekonomi, 2014)
State is an integral part of the budget, the government budget can run pemerintahaannya. Government can work well if all the existing budget can be met. Increasing tax revenues from the sector makes a ajor target for government programs, an increase in state revenue expected from the lack of awareness for the taxpayer to pay their obligations to the State the conditions that occur at this time, such as the level of public awareness is still lacking to pay taxes because they are stillconsidered it troublesome and complicated especially big calculation of income tax payable in order to increase state revenue then in 2013 the government implemented new income tax provisions stipulated in government Regulation (PP) No. 46 Year 2013, government policy is set on income Tax for Enterprises received or obtained by the taxpayer has certain Broto Circulation. Enforcement of Regulation No. 46 Year 2013, which is effective starting in June 2013, resulting in a loss of business, is subject to 1% of the turnover rate. Application of Regulation No. 46 of 2013 provides a major influence on the increase in income tax payable for Pharmacies, when compared calculated using progressive rates, the income tax payable for 2013 is Rp. 302 950. However, with the adoption of Regulation No. 46 Year 2013, the income tax payable are charged to pharmacies Mutia increased to Rp. 1.33285 million. An increase of 339.9%, or Rp. 1.02985 million in 2013 is an early feature that the application of Regulation No. 46 Year 2013 Taxpayers will find that the tax burden is too high because, the calculation of income tax payable based on turnover despite the efforts undertaken by the taxpayer does not make a profit. As for the corporate taxpayer or an individual taxpayer, the gross income exceeds USD. 4.8 billion per year in a tax year if the loss would not be taxable. It is clearly unfair for taxpayers whose income is below Rp. 4.8 billion per year, although procedures simplify the calculation of income tax payable taxpayer, whether the application of Regulation No 46 is a reward for small businesses or a sentence can be seen from the positive and negative impacts for taxpayers in addition to the presence of changing the behavior of the business world, where. Government Regulation No. 46 Year 2013 will have an impact that can not be avoided, because each policy will have a positive impact or a negative impact. Negative tendency of employers will decrease turnover rates or keep for not less than 4.8 M. This would be detrimental to the country because it will lower the opinion of the state that should be accepted.